Chlorhexidine varnish implemented treatment strategy for chronic periodontitis: A clinical and microbial study - D Manikandan (Journal of Pharmacy and Bioallied Sciences, 2016)
Aim: The aim of the present study was to evaluate the short-term clinical and microbiological effect of chlorhexidine varnish when used as an adjuvant to scaling and root planing in the treatment of chronic periodontitis. Materials and Methods: A split-mouth design was conducted in 11 patients suffering from chronic periodontitis. The control site underwent scaling and root planing, and the experimental site was additionally treated with chlorhexidine varnish application. Clinical parameters, namely, gingival index (GI), plaque index (PI), bleeding on probing (BoP), probing pocket depth (PPD), and clinical attachment level were recorded at baseline, 1 month, and 3 months postoperatively. Furthermore, microbial examination of the plaque samples was done at baseline, 1 month, and 3 months. Results: Both treatment strategies showed significant improvement in GI, PI, BoP, PPD, and clinical attachment level, at both follow-up visits by comparison with baseline levels. At study termination, chlorhexidine varnish implemented treatment strategy resulted in additional improvement in the clinical parameters, and more reduction in the total anaerobic count at 1 month and 3 months. Conclusions: These findings suggest that a chlorhexidine varnish implemented treatment strategy along with scaling and root planing may improve the clinical outcome for the treatment of chronic periodontitis in comparison to scaling and root planing alone.